2015
DOI: 10.1111/add.12970
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response relationship between methadone dose and adherence to antiretroviral therapy among HIV‐positive people who use illicit opioids

Abstract: Background and Aims For HIV-positive individuals who use illicit opioids, engagement in methadone maintenance therapy (MMT) can contribute to improved HIV treatment outcomes. However, to our knowledge, the role of methadone dosing in adherence to antiretroviral therapy (ART) has not yet been investigated. We sought to examine the relationship between methadone dose and ART adherence among a cohort of persons who use illicit opioids. Design and Setting We used data from the ACCESS study, an ongoing prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 74 publications
4
37
0
Order By: Relevance
“…83 In Vancouver, Canada, several longitudinal studies showed not only that OST continuation improved ART adherence over time, 84 but also the converse – that OST discontinuation significantly increased the risk of ART non-adherence 85 – and that OST patients with higher opioid agonist doses had the strongest adherence to ART. 86 In China, the understanding of the importance of the OST-ART link led to an effort to integrate ART services in methadone clinics. 87 While a number of practical challenges were encountered, the effort showed an appreciation for the value of integrating these areas of care.…”
Section: Drug Policy and Infectious Diseasesmentioning
confidence: 99%
“…83 In Vancouver, Canada, several longitudinal studies showed not only that OST continuation improved ART adherence over time, 84 but also the converse – that OST discontinuation significantly increased the risk of ART non-adherence 85 – and that OST patients with higher opioid agonist doses had the strongest adherence to ART. 86 In China, the understanding of the importance of the OST-ART link led to an effort to integrate ART services in methadone clinics. 87 While a number of practical challenges were encountered, the effort showed an appreciation for the value of integrating these areas of care.…”
Section: Drug Policy and Infectious Diseasesmentioning
confidence: 99%
“…In addition to standalone NSPs, pharmacies are a common source of syringes for prescription opioid injectors (Zaller et al, 2012). Medication-assisted treatment (MAT) with opioid agonists (methadone and buprenorphine) and antagonists (short- or long-acting naltrexone) have been shown to be highly effective at diminishing opioid use (Mattick, Breen, Kimber, & Davoli, 2009), decreasing the risk of HIV infection (Gowing, Farrell, Bornemann, Sullivan, & Ali, 2011), improving adherence with HIV medications (Lappalainen et al, 2015), and reducing the risk of mortality (Cornish, Macleod, Strang, Vickerman, & Hickman, 2010). Unfortunately, these medications are highly underutilized in the United States: of the 2.5 million persons with opioid dependence in 2012, fewer than one million received MAT (Volkow, Frieden, Hyde, & Cha, 2014).…”
Section: Harm Reduction For Extra-medical Prescription Opioid Usersmentioning
confidence: 99%
“…Evidence-based harm reduction may mitigate risk of death among HIV-positive PWID by reducing fatal overdose, as well as facilitating adherence to life-saving ART [48]. Studies undertaken in Vancouver, Canada, between 1996 and 2011 report a marked decline in rates of all-cause mortality among PWID [3**,29].…”
Section: Drug-related Fatalitiesmentioning
confidence: 99%
“…Such evidence highlights the sociostructural factors – including punitive laws, severe human rights abuse, inadequate prevention services, and stigma associated with IDU – impeding access to harm reduction worldwide [1**]. It is important to note that even in settings with access to OST, barriers to initiate OST (e.g., rigid intake criteria and lengthy waitlists) and maintain treatment (e.g., no individualization of treatment and no patient choice on medication and dose) [49] remain, which impacts ART adherence for HIV-positive PWID [48]. In light of the evidence of the efficacy of OST reducing drug-related fatalities, and facilitating access to life-saving ART, these impediments urgently need to be addressed.…”
Section: Drug-related Fatalitiesmentioning
confidence: 99%